STRATEGI PENGEMBANGAN MANAJEMEN KOPERASI DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA DI KOPERASI SIMPAN PINJAM HARAPAN MULYA BERSAMA - Surahman Hidayat; I Made Suardana; Zuriatin Hafizah (Nusantara Hasana Journal, 2025)
This study aims to analyze the management development strategy of the Savings and Loan Cooperative Harapan Mulya Bersama in improving member welfare. The research employed a descriptive qualitative method with data collection techniques including observation, interviews, questionnaires, and documentation. The findings indicate that the cooperative’s development strategy consists of long-term program planning, establishment of an efficient organizational structure, implementation of digital-based operations, strengthening of evaluation systems, and enhancement of human resource capacity. SWOT analysis resulted in an Internal Factor Analysis Summary (IFAS) score of 2.26 and an External Factor Analysis Summary (EFAS) score of 3.63, placing the cooperative in Quadrant I with an aggressive strategy. This position illustrates that the cooperative possesses sufficient internal strengths and is able to optimally exploit external opportunities. The application of aggressive strategies has contributed positively to member welfare through increased income, service satisfaction, active participation, and broader access to financing. Nevertheless, weaknesses remain in the form of limited digital technology utilization and insufficient entrepreneurship training. Therefore, strengthening aggressive strategies supported by technological advancement and member capacity building is expected to reinforce cooperative sustainability and expand its positive impact on member welfare.